Ortho-semantic learning of novel words: an event-related potential study of grade 3 children - Galilee, Alena; Beck, Lisa J.; Lownie, Clara J.; Veinot, Jennika; Mimeau, Catherine; Dempster, Tammy; Elliott, Laura M.; Deacon, S. Hélène; Newman, Aaron J. (Frontiers in Developmental Psychology, 2024)
Introduction As children become independent readers, they regularly encounter new words whose meanings they must infer from context, and whose spellings must be learned for future recognition. The self-teaching hypothesis proposes orthographic learning skills are critical in the transition to fluent reading, while the lexical quality hypothesis further emphasizes the importance of semantics. Event-related potential (ERP) studies of reading development have focused on effects related to the N170 component—print tuning (letters vs. symbols) and lexical tuning (real words vs. consonant strings)—as well as the N400 reflecting semantic processing, but have not investigated the relationship of these components to word learning during independent reading. Methods In this study, children in grade 3 independently read short stories that introduced novel words, then completed a lexical decision task from which ERPs were derived. Results Like real words, newly-learned novel words evoked a lexical tuning effect, indicating rapid establishment of orthographic representations. Both real and novel words elicited significantly smaller N400s than pseudowords, suggesting that semantic representations of the novel words were established. Further, N170 print tuning predicted accuracy on identifying the spellings of the novel words, while the N400 effect for novel words was associated with reading comprehension. Discussion Exposure to novel words during self-directed reading rapidly establishes neural markers of orthographic and semantic processing. Furthermore, the ability to rapidly filter letter strings from symbols is predictive of orthographic learning, while rapid establishment of semantic representations of novel words is associated with stronger reading comprehension.